A novel CPW-fed flexible antenna with circular polarization for enhanced vehicular communication systems - Rajesh Kumar D; Vaithianathan Venkatesan; Raja Periyasamy; B. Rubini; Ragunath G; Om Prakash Kumar; Shweta Vincent (Results in Engineering, 2025)
The rapid proliferation of advanced technology and the Internet of Things (IoT) has driven significant innovation in the design and development of flexible sensor antennas. This paper introduces a novel, highly flexible coplanar waveguide (CPW)-fed antenna tailored for vehicular applications. With a compact form factor of 27.5 × 53 × 0.1 mm³, the antenna demonstrates a broad impedance bandwidth of 5.5 to 6.5 GHz and a peak gain of 4.45 dBi, making it ideal for high-performance communication systems. A thorough bending analysis under various radii reveals robust flexibility and consistent performance, showcasing the antenna's adaptability to diverse operating conditions. The fabricated prototype exhibits excellent agreement between measured and simulated results, including a 100 % axial ratio bandwidth (ARBW), ensuring optimal circular polarization. These findings confirm the antenna's efficacy and reliability, making it a strong candidate for future vehicular communication systems.